Ecotoxicological assessment of pyriproxyfen under environmentally realistic exposure conditions of integrated vector management for Aedes aegypti control in Brazil. Issue 18 (16th September 2016) - Caixeta, Evelyn Siqueira; Silva, Carolina Fabiano; Santos, Vanessa Santana Vieira; Olegário de Campos Júnior, Edimar; Pereira, Boscolli Barbosa
ABSTRACT: There is increasing concern to control Aedes aegypti mosquito exposure in developing countries such as Brazil. Thus, integrated approaches using a combination of chemical, pyriproxyfen larvicide, and biological, Xiphophorus maculatus, larvivorous fish species approaches are necessary and important to initiate more effective control against mosquito borne diseases. This study describes the toxicological effects of pyriproxyfen larvicide on the fish Xiphophorus maculatus, the larvivorous fish species employed to destroy A. aegypti larvae mosquito species. The toxicological profile of pyriproxyfen was evaluated to determine compatible concentrations for the use of this chemical in conjunction with X. maculatus as an integrated approach against A. aegypti mosquito larvae. According to the behavioral responses of fish, the no-observed-effect concentration (NOEC) and lowest-observed-effect concentration (LOEC) of pyriproxyfen were determined to be 2.5 and 5 µg/L, respectively. Bioassays indicated that although pyriproxyfen was not lethal to X. maculatus, the application of this compound at a concentration reported to control the emergence of A. aegypti larvae may decrease the swimming performance of larvivorous fish and their ability to ingest A. aegypti L4 larvae. Data show that integration of biological larvivorous fish and chemical larvicides is more effective when the appropriate larvicide concentration is utilized.